Diagnóstico de situação da produção de linguiça frescal suína no município de Rio Verde/GO - Santos, Cinthia Yukico dos [UNESP] (2016)
The microbial contamination from food is one of the major public health problems. In food-producing establishments, the contamination of meat and meat food derived is very common. The aim of this study was to verify the sanitary hygienic conditions and physical structural from the establishments and also the microbiological quality of frescal swine sausages produced by institutions monitored by the Municipal Inspection Service of Rio Verde/Goiás. The research was divided into two parts, the first by means of technical audits in establishments with frescal swine sausage production with the application of a checklist to verify the sanitary conditions and physical-structural and application of a questionnaire for food handlers to verify the socioeconomic conditions and knowledge of GMP. The second part was developed by assessing of the microbiological quality of frescal swine sausages produced by the audited institutions. The establishments were classified according to the grades obtained the checklist as 2.2% (1/45) poor, 6.6% (3/45) regular, 70.0% (30/45) good, and 22, 2% (10/45) very good. The handlers interviewed had low educational level, 36% (18/50) with a complete high school, contrasting with 34% (17/50) with incomplete primary education, 58.0% (29/50) worked for over 10 years in butcher shops or slaughter houses, they had good hygiene habits and 68% of handlers participated in good Manufacturing Practices courses. It was found that the 45 frescal swine sausage samples analyzed 8.9% (4/45) exceeded the regulatory limit, and 2.2% (1/45) samples were positive for Staphylococcus coagulase positive, 6.6% (3/45) positive samples for thermotolerant coliforms and Staphylococcus positive coagulase concurrently. Based on these results, the adequacy of non-conformities is recommended, as the training of handlers and monitoring of the items evaluated. Some properties require an intensification of supervision in order to meet the regulatory requirements of quality meat products.